Identification of an Escherichia coli genetic locus involved in thermoregulation of the pap operon. - White-Ziegler, C A (1990)
We previously showed, using a single-copy papBAp-lac fusion (previously designated papBA-lac), that pyelonephritis-associated pili (pap) pilin gene transcription is subject to both phase variation and thermoregulatory control mechanisms (L. B. Blyn, B. A. Braaten, C. A. White-Ziegler, D. H. Rolfson, and D. A. Low, EMBO J. 8:613-620, 1989). At 37 degrees C, Escherichia coli strains carrying the papBAp-lac fusion displayed both Lac+ and Lac- colony phenotypes. In contrast, at 23 degrees C, colonies displayed a uniform Lac- phenotype, suggesting that pilin was not transcribed at this temperature. In this study, a strain carrying the papBAp-lac fusion was subjected to mini-Tn10 (mTn10) mutagenesis to isolate mutants that could initiate transcription of pilin at the nonpermissive temperature. Two classes of thermoregulatory mutants were identified in which the mTn10 mutation was linked to the mutant phenotype. Class I mutants displayed a phase variation phenotype at both 37 degrees C and 23 degrees C, whereas class II mutants displayed a uniform Lac+ colony phenotype at both temperatures. Preliminary analysis of these mutants showed that the mTn10 insertions in the class I mutants were chromosomally located, whereas the mTn10 insertions in the class II mutants were located within the papBAp-lac fusion phage. Southern blot analysis of the class I mutants demonstrated that mTn10 was present in the same 5.9-kilobase SalI DNA fragment in each mutant. Two of the class I mTn10 mutations were mapped to approximately 23.4 min on the E. coli K-12 chromosome. The locus defined by the class I mTn10 mutations was designated tcp, for thermoregulatory control of pap. Analysis of phase transition rates of the class I mutants showed that the phase-off (Lac-)----phase-on (Lac+) transition rates were higher than those observed with the nonmutant E. coli strain.